Novel peptides extracted from Muraenesox cinereus bone promote calcium transport, osteoblast differentiation, and calcium absorption - Jie Su; Tingru Chen; Dengyuan Liao; Yin Wang; Yongchang Su; Shuji Liu; Xiaoting Chen; Qian Ruifang; Linlin Jiang; Zhiyu Liu (Journal of Functional Foods, 2022)
Extracting peptides from fish bones as calcium supplements is of great significance for patients with osteoporosis. Novel peptides were obtained from Muraenesox cinereus bone (MCBP) by enzymatic hydrolysis and membrane separation. Molecular dynamics simulation and electron microscope analysis shown MCBP could chelate with calcium ions. A Caco-2 cell monolayer model was used to investigate the effect of peptide–calcium chelates on promoting calcium transport. MC3T3-E1 osteoblasts were treated with different concentrations of MCBP (0, 0.25, 0.5, or 1 mg/mL) to analyze the effects of MCBP on calcium absorption and cell differentiation factors. The bone formation of zebrafish evaluate the therapeutic effect of MCBP on the zebrafish OP model. The results showed that there were at least 13 kinds of calcium chelation modes in the mixed peptide, and peptide–calcium chelate could significantly improve calcium transport in the Caco-2 cell monolayer. After 14 days of culture with different concentrations of MCBP, the calcium deposition in MC3T3-E1 cells increased significantly. The type I collagen (COL-I), osteocalcin (OCN) and run-related transcription factor 2 (RUNX2), and activities of alkaline phosphatase (ALP) were dose-dependent with MCBP. MCBP can increase bone mineral density in an OP model of zebrafish. After being treated with MCBP, the expression levels of ALP, OCN, osteoprotegerin (OPG) and transforming growth factor-β (TGF-β) in the model group increased, while the expression levels of tartrate-resistant acid phosphatase (TRAP) decreased. The results indicated that MCBP may act as a nutritional food and provide an effective means for dietary supplementation in OP patients.